A democratising South Africa?: an analysis of the 2004 national election - Prudhomme, Leah Shianne (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2004)
Two of the post apartheid elections held in South Africa (1994, 1999) have been used as mechanisms to analyse and assess the extent to which the country's transition from apartheid to a democratic dispensation is succeeding or not. The primary analytical focus of the 1994 and 1999 elections has revolved around the nature of the party system and voting behaviour. Basically, contestation has arisen over two primary and related issues: the dominance of the African National Congress (ANC) weighed against the weakness of opposition parties and the implications that this development has for effective democratic consolidation. Also, whether voting decisions based on divisive racial and ethnic identities that underlie electoral contests are pervasive enough to derail the process of democratisation. Generally, the primary conclusion has been that the unfolding pattern of South African electoral politics indicates sufficient grounds on which to doubt the prospects for effective democratic consolidation. This dissertation engages these debates with particular reference to the 2004 elections. In contrast to this pessimistic view of the prospects of successful democratisation in South Africa it upholds through an analysis of the 2004 elections the view that there is insufficient empirical evidence, to conclude that South Africa's democratisation process is imperiled. It maintains that although there are problems related to the to the nature of the party system and some elements of voting behaviour there is enough countervailing evidence revealed by the 2004 election results that this does not present a substantially serious threat to the prospects of South Africa attaining a democratic society.
Keywords: African National Congress; Elections -- South Africa; Voting -- South Africa; Democracy -- South Africa; Political parties -- South Africa; South Africa -- Politics and government -- 1994-